Avaliação de metodologias de nível econômico de perdas - JONATHAN LYNCOLN ALVES BARBOSA (2021)
With the increasing level of water losses identified in distribution systems in Brazil, it is important to define goals and strategies to reduce losses to avoid high costs with water production, and to increase the revenues of water industry. But before arbitrarily defining targets and establishing loss reduction plans, it is necessary to evaluate to what level it is feasible to reduce these losses. This level is called the Economic Level of Losses, and it defines the optimal level where the system will have higher revenues and lower costs. There are different methodologies that can be applied, some are practical, and others are complex. This work presents a study about the concept of economic level, and an evaluation of methodologies along with their application, with the proposal of determining if it is viable to use them. Results were collected from the calculations performed and it was concluded that operations can take advantage of these analyses because they collaborate with the definition of loss reduction objectives. In tests carried out, it was possible to observe that if a system reduces its losses up to the calculated level, it will have its revenue and operational cost optimized, despite the increments in losses control actions. As future studies, it was proposed that data collection fields should be improved, to boost their quality so that analyses such as these can have more reliable results.